Sleepiness - Ellenbogen, Jeffrey M. (Seminars in Neurology, 2016)
Sleep medicine can be a particularly rewarding clinical area for neurologists. After all, the driving organ of sleep is the brain. Many of the sleep disorders are primary brain disorders, whereas other sleep disorders (and their medications) influence brain function. But without an organized approach, even the engaged and motivated neurologist can easily become frustrated when dealing with patients whose concerns center on an undesirable degree of sleepiness. Lost in the thicket of information provided during the patient–doctor encounter, many physicians are unable to direct the history toward particular diagnostic hypotheses. So, rather than provide an exhaustive and disorganized set of details about sleep medicine, the author instead shares pearls of sleep medicine in the context of an overall framework, with the goal to foster targeted history-taking for the successful diagnosis of a patient struggling with maintaining wakefulness. The topic of excessive sleepiness will be covered because it is so common and because its mastery is fundamental to approaching most patients with sleep disorders. Common and important pitfalls regarding the topic of sleepiness—and how to avoid them—will be discussed. Misdiagnoses and mismanagement are easy to avoid if this entire framework is kept in mind.
Keywords: sleep; sleepiness; drowsy; fatigue; narcolepsy